Analisis Faktor-Faktor Yang Mempengaruhi Kemiskinan Di Kabupaten/Kota Jawa Tengah - Widiastuti, Angga Tri; , Eni Setyowati, M.Si (2016)
Poverty is one of the problems in the economy are complex and multidimensional. Therefore necessary ti find solutions to overcome or at least reduce the level of poverty. This study aimed to analyze the influence of the GDP, the level unemploymen t, population and IPM on poverty in Central Java from 2013. The method used in this research is multiple linear regression analysis was used t o determine the direction of the dependent variable and independent variable associated positive or negative and using secondary data type. Region in this research is to look at variations in the level of poverty in 35 district / town in Central Java. To measure variations in the results obtained are quite variable signifikan. Results of the GDP, population, and IPM significant effect. Terefore development the GDP, population and IPM should be considered to adrdress the problem of poverty.